2020
DOI: 10.3390/cells9040801
|View full text |Cite
|
Sign up to set email alerts
|

A Regulatory Noncoding RNA, nc886, Suppresses Esophageal Cancer by Inhibiting the AKT Pathway and Cell Cycle Progression

Abstract: nc886 is a regulatory non-coding RNA (ncRNA) whose expression is frequently silenced in malignancies. In the case of esophageal squamous cell carcinoma (ESCC), nc886 silencing is associated with shorter survival of patients, suggesting nc886’s tumor suppressor role in ESCC. However, this observation has not been complemented by an in-detail study about nc886’s impact on gene expression and cellular phenotypes. Here we have shown that nc886 inhibits AKT, a key protein in a renowned pro-survival pathway in cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
(50 reference statements)
0
13
0
Order By: Relevance
“…Thus far, only a few fragmentary functions of the vault complex have been identified including the assembly of the nuclear pore complex [ 102 , 103 ] or roles in innate immunity [ 104 , 105 ]. It was reported that the expression levels of the vault complex components such as vtRNAs and MVP varied in several cancer cells [ 46 , 68 , 83 , 85 , 86 , 106 , 107 , 108 , 109 , 110 ]. Furthermore, the intracellular localization of the vault complex tends to be changed from the cytoplasm to the nucleus in response to external stresses or stimuli, which are involved in tumorigenesis [ 26 , 111 ].…”
Section: Mvp and The Vault Complex: Implications To Cell Proliferatio...mentioning
confidence: 99%
“…Thus far, only a few fragmentary functions of the vault complex have been identified including the assembly of the nuclear pore complex [ 102 , 103 ] or roles in innate immunity [ 104 , 105 ]. It was reported that the expression levels of the vault complex components such as vtRNAs and MVP varied in several cancer cells [ 46 , 68 , 83 , 85 , 86 , 106 , 107 , 108 , 109 , 110 ]. Furthermore, the intracellular localization of the vault complex tends to be changed from the cytoplasm to the nucleus in response to external stresses or stimuli, which are involved in tumorigenesis [ 26 , 111 ].…”
Section: Mvp and The Vault Complex: Implications To Cell Proliferatio...mentioning
confidence: 99%
“…Due to its importance for cancer biology, vtRNA2-1 transcriptional regulation was recently more investigated ( Yeganeh & Hernandez, 2020 ). Various studies reported tissue specific roles of vtRNA2-1 in normal ( Golec et al , 2019 ; Lee et al , 2019 ; Miñones-Moyano et al , 2013 ; Sallustio et al , 2016 ; Suojalehto et al , 2014 ) and cancer tissues ( Ahn et al , 2018 ; Fort et al , 2018 ; Hu et al , 2017 ; Im et al , 2020 ; Jeon et al , 2012a ; Kunkeaw et al , 2012 ; Lee et al , 2011 ; Lee, 2015 ; Lee et al , 2016 ; Lee et al , 2014a ; Lee et al , 2014b ; Lei et al , 2017 ; Li et al , 2017 ; Ma et al , 2020 ; Treppendahl et al , 2012 ) and epigenetic alterations of the locus have been described in different malignancies ( Ahn et al , 2018 ; Cao et al , 2013 ; Fort et al , 2018 ; Helbo et al , 2015 ; Helbo et al , 2017 ; Joo et al , 2018 ; Lee et al , 2014a ; Lee et al , 2014b ; Park et al , 2017a ; Romanelli et al , 2014 ; Treppendahl et al , 2012 ). Meanwhile, except for Kirsten Grønbæk group´s contributions on the chromatin characterization of vtRNA1-3 and vtRNA1-2 promoters ( Helbo et al , 2015 ; Helbo et al , 2017 ), little is known about the transcriptional regulation and expression of the other vtRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, vtRNA2-1 was proposed as a new type of ncRNA functioning as a tumor suppressor gene (TSG) that inhibits PKR, and was consequently renamed as “nc886” ( Golec et al , 2019 ; Jeon et al , 2012a ; Jeon et al , 2012b ; Lee et al , 2011 ). Then, its anti-proliferative and TSG function was described in prostate ( Aakula et al , 2016 ; Fort et al , 2018 ; Ma et al , 2020 ), skin ( Lee et al , 2019a ), gastric ( Lee et al , 2014b ) esophageal ( Im et al , 2020 ; Lee et al , 2014a ) and cholangiocarcinoma cells ( Kunkeaw et al , 2012 ). Conversely, a pro-proliferative and anti-apoptotic oncogenic role was proposed for vtRNA2-1 in renal ( Lei et al , 2017 ), ovarian ( Ahn et al , 2018 ), thyroid ( Lee et al , 2016 ), cervical ( Li et al , 2017 ) and endometrial ( Hu et al , 2017 ) tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its importance for cancer biology, vtRNA2-1 transcriptional regulation was recently more investigated (Yeganeh and Hernandez, 2020). Various studies reported tissue specific roles of vtRNA2-1 in normal (Golec et al, 2019;Lee et al, 2019a;Miñones-Moyano et al, 2013;Sallustio et al, 2016;Suojalehto et al, 2014) and cancer tissue (Ahn et al, 2018;Fort et al, 2018;Hu et al, 2017;Im et al, 2020;Jeon et al, 2012a;Kunkeaw et al, 2012;Lee et al, 2011;Lee, 2015;Lee et al, 2016Lee et al, , 2014aLee et al, , 2014bLei et al, 2017;Li et al, 2017;Ma et al, 2020;Treppendahl et al, 2012) and epigenetic alterations of the locus have been described in different malignancies (Ahn et al, 2018;Cao et al, 2013;Fort et al, 2018;Helbo et al, 2015Helbo et al, , 2017Joo et al, 2018;Lee et al, 2014aLee et al, , 2014bPark et al, 2017;Romanelli et al, 2014;Treppendahl et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, vtRNA2-1 was proposed as a new type of ncRNA functioning as a tumor suppressor gene (TSG) that inhibits PKR, and was consequently renamed as "nc886" (Golec et al, 2019;Jeon et al, 2012aJeon et al, , 2012bLee et al, 2011). Then, its anti-proliferative and TSG function was described in prostate (Aakula et al, 2015;Fort et al, 2018;Ma et al, 2020), skin (Lee et al, 2019a), gastric (Lee et al, 2014b) and esophageal (Im et al, 2020;Lee et al, 2014a) and cholangiocarcinoma cells (Kunkeaw et al, 2012). Conversely, a pro-proliferative and anti-apoptotic oncogenic role was proposed for vtRNA2-1 in renal (Lei et al, 2017), ovarian (Ahn et al, 2018), thyroid (Lee et al, 2016), cervical (Li et al, 2017) and endometrial (Hu et al, 2017) tissues.…”
Section: Introductionmentioning
confidence: 99%